Differences in handgrip strength-endurance and muscle activation between young male judo athletes and untrained individuals - de Caldas Honorato, R.; Franchini, E.; Petrovna Resende Lara, J.; Fonteles, A. I.; Barbosa de Lima Pinto, J. C.; Mortatti, A. L. (Research Quarterly for Exercise and Sport, 2021)
Purpose: The aim of this study was to compare strength-endurance handgrip performance and muscle coactivation between judo athletes and untrained young males. Method: The sample was 38 judo athletes and 38 untrained young males, between 12 and 15 years-old. Maturational status was evaluated by age at peak height velocity. A maximal isometric handgrip test (three 5-s repetitions, with 90-s intervals) and an isometric strength-endurance handgrip test (ten 10-s all-out isometric handgrip repetitions, 20-s intervals) was conducted in dominant (D) and nondominant (ND) hands, using a dynamometer with EMG monitor to detect muscle activation. Results: ANCOVA analysis, controlling for maturational status, showed that judo athletes had higher values of maximal absolute (D = 33.6 ± 8.9 kgf vs 29.1 ± 9.0 kgf; ND = 33.8 ± 9.9 kgf vs 28.1 ± 8.1 kgf) and relative strength to body mass (D = 0.64 ± 0.12 kg/kgf vs 0.57 ± 0.13 kg/kgf; ND = 0.64 ± 0.16 kg/kgf vs 0.56 ± 0.14 kg/kgf). Moreover, judo athletes presented lower strength mean fatigue index (33.2 ± 6.9 % vs 37.9 ± 8.7 %) and muscle coactivation (48 ± 19.8 % vs 57.5 ± 22 %), only in the dominant hand, during the isometric strength-endurance handgrip test. During all repetitions of isometric endurance test there were no group or interaction between factors effects for absolute strength, relative strength and muscle coactivation. Conclusion: In summary, judo athletes present higher maximal absolute and relative strength and strength-endurance performance, concomitantly with decreased muscles co-activation (primary in dominant hand) during handgrip tests.